Depositional Environment and Reservoir Prospect Analysis of Barail Sandstone Exposed in the Northeastern Part of Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The study characterized the Oligocene Barail sandstone in the Surma Basin from a reservoir perspective. Data were collected by direct field observations; rock samples were collected from outcrops for detailed sedimentological, petrographic, and geochemical analysis. Collected sedimentary logs are analyzed to delineate the facies associations, sandbody architecture, and depositional environment. A total of ten facies were identified, which were further grouped into three facies associations: FA1: Tidal-influenced multistorey channel-fill deposits, FA2: Fluvial multistorey channel-fill deposits, and FA3: Overbank deposits. Facies analysis suggests that the Barail sandstone was deposited in the tidal-influenced paralic to fluvial depositional settings, and channel body dimensions increase towards the top. A petrographic study shows that these sandstones are mostly litharenite (Q70F4L26) in type, and sediments were derived from quartzose recycled orogens. The average porosity of the sandstones is 16.9%; the pore spaces are of both primary and secondary origin and are mostly interconnected. Porosity distribution in the fluvial multistory channel-fill deposits (FA2)—the upper part of the sandstone succession, is less heterogeneous, while that in the tidal-influenced channel-fill deposits (FA1), occurs in the lower part is more heterogeneous. Both the depositional process and diagenesis influenced the porosity of Barail sandstones. Geochemical analysis suggests that the sandstones are chemically stable and moderately matured. The study demonstrates that the Barail sandstones may be a good petroleum reservoir.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(1), 2023, P 69-88